Konkurencyjność produkcji żywności w warunkach globalizacji - Spychalski, Grzegorz (Food Production Competitiveness in the Globalisation Process, 2006)
The paper presents the main dilemmas of food production development in the context of оbserved globalisation processes. Internalisation of economic activity in connection with dynamic growth of world trade facilitates competitiveness increase of all sectors and branches of economy. Agriculture as a foundation for food manufacturing is not quite in this process because of special protection from economic policy. While food processing sector and distribution system are fully liberalised, the farming is still at the beginning of important reforms. The chances of the acceleration are located in the World Trade Organisation negotiations about food trade conditions. The change of agricultural policy will cause the increase of the World Gross Domestic Product and allow for export development among countries with the lowest costs of production. At the same time general costs of agricultural policy will decrease and redistribution of total income will be smaller on national and international level.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 332-338